2016
DOI: 10.18805/ijar.10278
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of genetic variations among native andsome local chicken populations in Turkey

Abstract: Genetic variations among native and local chicken populations in six different locations across Turkey were established using 15 ISSR primers, and produced 87 bright and reproducible bands. According to pairwise genetic differentiation among the populations (G ST ), the highest genetic differentiation was determined between the Samsun and Yozgat population and the lowest was observed between the Dulkadirli and Budak populations. Shannon's index was calculated to be 0.239. The gene flow (Nm) among the populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The predicted heterozygosity scores for diverse loci were about 0.655 to 0.884 with an average score of 0.796 (Table 4). In a previous study, it was shown that the average genetic diversity of Nei (H) (Nei 1987) varied in various animals, i.e., 0.0655 in goats, 0.2076 in sheep (Askari et al 2011), and 0.118 in chicken (Tunca and Taskin 2016). Values of the effective quantity of alleles (Ne) in this duck were about 2.8 to 6.6, higher than goat (1.1085 ± 0.2624), sheep (1.3673±0.4050) (Askari et al 2011), chicken (0.157), mink (1.5180) (Hong-yan et al 2013), and Anatolian duck (1.26) (Tunca et al 2015).…”
Section: Genetic Diversitymentioning
confidence: 97%
“…The predicted heterozygosity scores for diverse loci were about 0.655 to 0.884 with an average score of 0.796 (Table 4). In a previous study, it was shown that the average genetic diversity of Nei (H) (Nei 1987) varied in various animals, i.e., 0.0655 in goats, 0.2076 in sheep (Askari et al 2011), and 0.118 in chicken (Tunca and Taskin 2016). Values of the effective quantity of alleles (Ne) in this duck were about 2.8 to 6.6, higher than goat (1.1085 ± 0.2624), sheep (1.3673±0.4050) (Askari et al 2011), chicken (0.157), mink (1.5180) (Hong-yan et al 2013), and Anatolian duck (1.26) (Tunca et al 2015).…”
Section: Genetic Diversitymentioning
confidence: 97%
“…al.., 2007 the eukaryote genome and highly polymorphic being adequate to characterize and estimate genetic distance between population, allowing the comparison between races and the comprehension of the nature of avian biodiversity (ABOU-EMERA et al, 2017). The ISSR marker is of simple use, besides being cheaper than SSR, don't need previous knowledge of the genome and might be more frequently used in the future on research of chicken or birds in general due to these advantages (TUNCA & TASKIN, 2016). However, ISSR is characterized by being a dominant marker and the presence of amplified fragment might mean a dominant homozygous or heterozygous, while its absence represents a recessive homozygous, because is lowest informative than SSR; uhowever, been useful for characterization of genetic structure, mainly in preliminary studies (COSTA et al 2015).…”
Section: Granevit Ze 2007mentioning
confidence: 99%
“…The table 2 also demonstrated that researches involving molecular markers and chicken aimed to assess the level of genetic variability in populations from different places, highlighting any possible distinction between chickens under different environments. These studies are essentials when the aim is to maintain genetic variability to be useful in future crosses (TUNCA & TASKIN, 2016).…”
Section: Granevit Ze 2007mentioning
confidence: 99%